EDUCATIONAL AND SOCIO-ECONOMIC ISSUES JAPANESES BRAZILIANS IN JAPAN (Revista de Letras Norte@mentos, 2017)
It is now 27 years since revised immigration laws brought some 300,000 Japanese-descendantNikkei Brazilians to Japan for economic opportunities. Brazilian schools were preferred tomaintain Portuguese before the 2008 worldwide depression, which also forced many ​Nikkeifamilies to return home. Presently, in the so called ‘Second Generation Resident Brazilians’ age,more ​Nikkei children attend Japanese public schools hoping for higher education. Economic andeducational gaps among the youth have widened. Some can attend college and others havebecome economically and linguistically stateless. This paper explores educational andsocio-economic ​ ​issues ​ ​that ​ ​Japanese ​ ​Brazilians ​ ​in​ ​Japan​ ​have ​ ​faced​ ​to​ ​enjoy​ ​full ​ ​citizenship.